Spontaneous coronary artery rupture presenting as an acute coronary syndrome evolved in pseudoaneurysm and cardiac tamponade: Case report and literature review. Issue 7 (1st October 2017) - Longobardi, Antonio; Iesu, Severino; Baldi, Cesare; Di Maio, Marco; Panza, Antonello; Mastrogiovanni, Generoso; Masiello, Paolo; Itri, Francesco; Lambiase, Catello; Bossone, Eduardo; Piscione, Federico; Di Benedetto, Giuseppe
Abstract: Spontaneous coronary artery rupture is a rare disorder that may develop early into a sudden death due to the abrupt evolution of the associated cardiac tamponade. In some cases the rupture is contained and a false aneurysm develops with slower evolution of clinical signs. The correct diagnosis of spontaneous coronary artery rupture deserves a high level of suspicion; frequently it may be missed because the time window of its evolution seems to be very short or signs of acute coronary syndrome sometimes can prevail, leading to delays in diagnosis or to misdiagnosis. We report the case of a patient presenting a giant pseudoaneurysm of the right coronary artery due to spontaneous coronary artery rupture without any underlying disease. Moreover we present a review of the few cases in the literature, offering a pathophysiological hypothesis linking the site of rupture and clinical presentation.